Survey of National Approaches to Practice in Local Anaesthetic Rhinology Surgery ( SNAP ‐ LARS ): A United Kingdom National Cross‐Sectional Collaborative Survey - Dhruv Patel; Behrad Barmayehvar; Shayan Shahidi; Tharsika Myuran; Ding Yang; Vikas Acharya; Miran Pankhania; Raj K. Bhalla; Ashok Rokade (Clinical Otolaryngology, 2026)
ABSTRACT Introduction Local anaesthetic rhinology surgery (LARS) offers a safe and cost‐effective alternative to procedures traditionally performed under general anaesthesia. Despite publication of British Rhinological Society guidance in 2022, the landscape of LARS provision in the United Kingdom (UK) remains unclear. This study aimed to characterise current practice, whilst highlighting variations and perceived barriers to LARS. Methods A cross‐sectional national multi‐centre collaborative survey was conducted between October 2025 and February 2026. The protocol followed the CROSS reporting checklist for survey studies. Only endonasal procedures were included. Each response captured a consultant's typical LARS practice over the preceding 12 months. Free‐text responses underwent thematic analysis. Results Sixty‐three consultant responses from 39 sites were analysed. The most frequently performed procedures were endonasal biopsy ( n = 60, 95.2%), septal button insertion ( n = 46, 73.0%) and nasal polypectomy ( n = 35, 55.6%). Most consultants performed ≤ 30 cases annually (76.2%) and typically ran one LARS session per month (76.2%). Most cases (76.6%) were performed in operating theatres. Sedation was offered by 19.0% ( n = 12), and most patients were discharged within 2 h ( n = 57, 90.5%). Routine PROM collection was only reported by 49.2% ( n = 31). Utilisation of reusable equipment varied widely, with 47.6% ( n = 30) using ≤ 50% reusable equipment. Barriers to service expansion included space, equipment, staffing and funding. Conclusion LARS is delivered through heterogeneous models, and responses showed skew towards England. There is considerable opportunity to expand outpatient procedure‐room delivery, standardise care pathways and outcome measurement, and address organisational barriers. These could enhance efficiency, reduce costs, minimise environmental impact, and ultimately improve patient experience.